The Utilization and Obstacles of Online Learning Applications - Sri Marmoah; Devina Kusuma Wardani (Universitas Pendidikan Ganesha, 2023)
The use of online learning applications is constrained by the abilities of teachers and the lack of facilities and infrastructure that affect student learning outcomes. This study aims to analyze the use of applications during the online learning process and the obstacles encountered during that process. The approach used is descriptive qualitative. The subjects of this study were the teachers of grades 4, 5, and 6. Observations, interviews, and documentation are the data collection techniques used in this study. The data obtained were then analyzed qualitatively by means of data reduction, data presentation, and drawing conclusions. The results of this study show that, first, the online learning process uses the WhatsApp application for communication, attendance, and opening. YouTube application to explain material if learning is carried out non-face-to-face (asynchronous). Google Meet and Zoom applications for virtual (synchronously) face-to-face learning. The Google Classroom, Google Form, and Quiz applications are used for assessment when evaluating learning. Second, the obstacles to using the application are low learning concentration, low learning outcomes, low self-confidence, and a lack of facilities for using online applications. The results of this study are useful for overcoming problems regarding the use of online learning applications.